2010
DOI: 10.1002/ijc.24929
|View full text |Cite
|
Sign up to set email alerts
|

Combination of p53 codon 72 polymorphism and inactive p53 mutation predicts chemosensitivity to 5‐fluorouracil in colorectal cancer

Abstract: There are increasing reports showing the clinical significance of the p53 polymorphism status in terms of the response to chemotherapy. We investigated whether p53 polymorphism and mutation were associated with in vitro sensitivity to 5-fluorouracil (5-FU) in patients with colorectal cancer. Chemosensitivity to 5-FU was evaluated by the collagen gel droplet embedded culture drug sensitivity test. 5-FU sensitivity of tumor cells without inactive p53 mutation in the arginine/arginine (Arg/Arg) variant was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…Therefore, p38MAPK could be included in a future list of putative prognosis markers for 5-FU-based therapy, as it is the case of apoptotic proteins (Hector and Prehn, 2009). In view of the connection between p53, a known marker of 5-FU-based therapy even at the clinical level (Nabeya et al, 1995;Zheng et al, 1999;Tominaga et al, 2010), and p38MAPK signaling pathway, it seems logical to consider further studies to fully establish the role of p38MAPK as a biomarker for 5-FU-based therapy. Thus, and considering previous evidences with ara-C (Sanchez-Arevalo, et al, 2005), we demonstrate a major role for the p38MAPK signaling pathway in antimetabolites-based therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, p38MAPK could be included in a future list of putative prognosis markers for 5-FU-based therapy, as it is the case of apoptotic proteins (Hector and Prehn, 2009). In view of the connection between p53, a known marker of 5-FU-based therapy even at the clinical level (Nabeya et al, 1995;Zheng et al, 1999;Tominaga et al, 2010), and p38MAPK signaling pathway, it seems logical to consider further studies to fully establish the role of p38MAPK as a biomarker for 5-FU-based therapy. Thus, and considering previous evidences with ara-C (Sanchez-Arevalo, et al, 2005), we demonstrate a major role for the p38MAPK signaling pathway in antimetabolites-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major problems associated with 5-FU therapy is the development of resistance to the drug. Resistance to 5-FU may occur by a number of mechanisms, including alterations in the enzymes implicated in the metabolism or in the mechanism of action of the drug, especially in the target enzyme (for review, see Peters et al, 2002), also, alterations in molecules such as p53 (Lowe et al, 1993;Bunz et al, 1999;Longley et al, 2002;Tominaga et al, 2010) and in proteins critical in the response to DNA damage, such as ataxia telangiectasia mutated (ATM) or ataxia telangiectasia and Rad3 related (ATR) (for review, see Wyatt and Wilson III, 2009). For example, ATR has been shown to be an essential mediator in the antitumoral properties of 5-FU (Wilsker and Bunz 2007) through the control exerted on the mismatch repair system (Liu et al, 2008) or on CHK1, a regulatory component of the DNA damage checkpoint (Jardim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, mild manifestations of non-alcoholic fatty liver disease (NAFLD) after 5FU [26], more serious non-alcoholic steatohepatitis after irinotecan and sinusoidal obstruction syndrome (SOS) after oxaliplatin-based treatment [27] have been recorded. Using the same biomarkers as in our study, Panasiuk and colleagues [28] showed that the intensification of inflammation in NAFLD may also impact on biomarker expression in human hepatocytes with the induction of pro-apoptotic protein p53 and the inhibition of anti-apoptotic Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…The role of p53 in preventing colon cancer progression and improving patient response to therapy is well-documented [2529]. The pharmacological enhancement of p53 activity in colon cancers maintaining a functional p53 gene may therefore be an effective and relatively safe therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%